Lithofacies of the Halang Formation in the Cijurey River-Majalengka - Abdurrokhim, .; Firmansyah, Yusi; Natasia, Nanda; Saputra, Mulyana (Journal of Geological Sciences and Applied Geology, 2017)
This report discusses lithofacies composition of the upper part Halang Formation that is well exposed along the Cijurey River, Majalengka - West Java.  A total of 450-m-thick continues section of the Halang Formation have been measured and described. The lithofacies composition of the Halang Formation in the Cijurey River consists of alternating thin- to very thin-bedded sandstones and mudstone, un-bedded mudstones, very thick pebbly mudstones, breccia and slump. Andesitic igneous rock intruded locally to this formation.